Furosemide induced bullous pemphigoid: a case report - D., Venu; R., Vijendra (International Journal of Basic & Clinical Pharmacology, 2019)
Bullous pemphigoid is an acquired autoimmune disease characterized by subepidermal vesicles and bullae. The etiology is mostly idiopathic with the highest occurrence in elderly patients. However, it is now well-accepted that bp has been triggered by or associated with drug therapy. Over 50 agents have been implicated as a cause of Drug-induced bullous pemphigoid, including diuretics, ace inhibitors, and antibiotics. We present a case of Bullous pemphigoid in a 75 year old male probably induced by furosemide. A 75 year old male was admitted to the dermatology department of KIMS hospital, Bengaluru. Presented with multiple tense bullae and vesicles over both upper limbs, forearm and few collapsed bullae and vesicles over the extensor aspect of forearm. Patient had a past history of myocardial infarction and undergone coronary artery bypass grafting for the same and treated with multiple medications. Among the treatment given injection furosemide was the one of the drug, after which he developed lesions and also presented with fluid filled bullae. A diagnosis of bullous pemphigoid was made based on clinical history and was treated with prednisolone, halobetasol and antibiotics. The lesions improved significantly with the above management and patient recovered enough to be discharged from the hospital after 5 days. Severe and serious reactions such as bullous pemphigoid can be caused by used drugs like furosemide.